Mobile eye-exercise matasehatku application to reduce asthenopia in office workers: a quasi-experimental study - Habiba, Putri Ghanim Septia; Jaya, Akbar (Universitas Muhammadiyah Purwokerto, 2025)
Background: Asthenopia is common among computer users, yet limited evidence exists regarding interventions targeting office workers. Mobile health technologies offer new opportunities to promote ocular health in technology-intensive work environments. Purpose: This study aimed to evaluate the effectiveness of the MataSehatKu mobile eye-exercise application in reducing asthenopia among office workers in the information technology sector. Method: A quasi-experimental pre-test–post-test control group design was conducted with 39 office workers (17 intervention, 22 control) selected by purposive sampling. Asthenopia levels were measured using the Digital Eye Strain Questionnaire (DES-Q) before and after a two-week intervention. Result: The intervention group showed a significant reduction in mean asthenopia scores (8.82 ± 5.13 to 2.71 ± 1.96; mean decrease = 6.11; p < 0.001), while the control group showed a significant increase (12.45 ± 9.10 to 19.82 ± 12.91; mean increase = 7.36; p < 0.001). Between-group post-test comparison revealed significantly lower scores in the intervention group (p < 0.001). Effect size analysis indicated a large impact (Cohen’s d = 1.57 within-group; d = 1.74 between-groups). Conclusion: The MataSehatKu application effectively reduced asthenopia among office workers, supporting the potential of mobile health–based eye-exercise programs as scalable occupational health strategies.